EFFECT OF STYLES OF LEADERSHIP AND DISCIPLINE ON EMPLOYEES PERFORMANCE ON EMPLOYEES PT. PERKEBUNAN NUSANTARA II TANJUNG MORAWA - Fazhil Hanafi Asnora (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2018)
Leadership is necessary when an organization wants to succeed. Moreover, good employees are always curious about how they can contribute to the achievement of organizational goals and, at least, the passion of employees requires leadership as a basis for external motivation to keep their goals in harmony with organizational goals. The purpose of this study is to determine the style of leadership and work discipline affect the performance of employees at PT. Perkebunan Nusantara II Tanjung Morawa. The research used multiple linear regression technique. The results showed that the variables of leadership style and work discipline affect positively and significantly on the performance of employees simultaneously. Partially leadership style has a significant effect on employee performance, while work discipline has no significant effect on employee performance. R Square is 0.192. This shows that the variables X1 and X2 explain to variable Y is 19.2% and the rest of 80.8% is determined by other factors outside the independent variables of this study such as delegation of authority, employee maintenance, incentives